Can artificial intelligence reduce the effect of independence conflicts on audit firm liability? - Libby, Robert; Witz, Patrick D. (Contemporary Accounting Research, 2024)
Abstract In this study, we examine whether the use of artificial intelligence (AI) can reduce the effect of independence conflicts on audit firm liability. In two experiments, we manipulate (1) whether procedures are performed by a human auditor or with AI and (2) whether the audit firm was careful in maintaining the appearance of independence from the audit client. Results of both experiments indicate that the use of AI significantly reduces the impact of the appearance of independence conflicts on jurors' judgments of audit firm liability. When concerns relating to the appearance of independence conflicts are present, the use of AI helps maintain the perceived objectivity of the auditor, which results in jurors maintaining higher overall trust in the audit process. Our study contributes to literature on determinants of auditor litigation risk and how technological change that is likely to grow in prominence might affect audit firm liability.